The Life of an Editor: Dr. Russell Van Gelder, MD, Ph.D., Editor in Chief of Ophthalmology, the Journal of the American Academy of Ophthalmology - Malina Cernatescu; Juan C. Puyana; Francisco J. Bonilla-Escobar (University Library System, University of Pittsburgh, 2023)
In this insightful interview article, we delve into the life and role of Dr. Russell Van Gelder, MD, Ph.D., Chair of the Ophthalmology Department at the University of Washington and Editor in Chief of Ophthalmology, the Journal of the American Academy of Ophthalmology. Driven by a profound passion for literature, he emphasizes the enduring impact of scientific publications as fundamental to knowledge. He views curating this literature as a privileged responsibility, ensuring its enduring quality. Dr. Van Gelder acknowledges the complexities of predictive editing and the challenges of identifying impactful papers. He let us dig into the editorial process at Ophthalmology as we learn about its rigor, involving meticulous screening, comprehensive reviews, and constructive feedback. For aspiring editors, he underscores the importance of a genuine love for literature and the value of constructive criticism. Dr. Van Gelder addresses common misconceptions about the editor's role, highlights the ethical aspects of publishing, and advocates for a focus on content quality, especially in a world marked by predatory practices. He shares a memorable encounter with the work of Clyde Keeler, a scientist from the early 20th century, underlining the timeless nature of literature as a repository of knowledge that transcends generations. In essence, Russ, as affectionately referred to by colleagues, offers a deep understanding of the life of an editor dedicated to preserving the integrity and excellence of scientific publications in the field of ophthalmology. His perspective is distinctively important for medical students and early careers physicians, underscoring the crucial role that editors play in the advancement of scientific knowledge.